2014
DOI: 10.1074/jbc.m114.554071
|View full text |Cite
|
Sign up to set email alerts
|

TMTC1 and TMTC2 Are Novel Endoplasmic Reticulum Tetratricopeptide Repeat-containing Adapter Proteins Involved in Calcium Homeostasis

Abstract: Background:The ER is organized into subdomains containing large protein complexes that help to perform a variety of functions. Results: TMTC1 and TMTC2 are ER membrane proteins with large TPR-containing adapter domains that mediate associations with SERCA2B. Conclusion: TMTC1 and TMTC2 are ER adapter proteins that influence intracellular calcium levels. Significance: TMTC1 and TMTC2 are regulators of calcium homeostasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
60
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 44 publications
2
60
0
Order By: Relevance
“…TMTC2 is expressed in many tissues (Wu, MacLeod, & Su, 2013) including the inner ear (Runge et al, 2016). While the specific function(s) of TMTC2 within the auditory system remain unknown, the protein is likely to affect ion currents and membrane potential in inner ear cells, based on reported functions in other cell types (Sunryd et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…TMTC2 is expressed in many tissues (Wu, MacLeod, & Su, 2013) including the inner ear (Runge et al, 2016). While the specific function(s) of TMTC2 within the auditory system remain unknown, the protein is likely to affect ion currents and membrane potential in inner ear cells, based on reported functions in other cell types (Sunryd et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The motif is found in a number of proteins and mediates protein-protein interaction (http://www.uniprot.org/keywords/KW-0802). A previous study 20 localized TMTC2 to the endoplasmic reticulum in HEK293 cells and found it to be associated with the endoplasmic reticulum calcium uptake pump SERCA2B, but the detailed function of the protein and its putative role in other tissues have not been elucidated. It is possible that TMTC2 is involved in a novel mechanism that affects hearing in humans.…”
Section: Discussionmentioning
confidence: 99%
“…TMTC3 and TMTC4 are present in the chordata phylum and recent analysis shows that they are conserved in protists (Larsen et al, 2019). Like TMTC1 and TMTC2, TMTC3 and TMTC4 are divided into two regions that appear to create distinct domains, an N-terminal hydrophobic region and a Cterminal domain consisting of large TPR clusters (Sunryd et al, 2014). ΔG predicts that TMTC3 and TMTC4 have ten and twelve potential transmembrane domains, respectively (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A new putative family of O-mannosyltransferases was recently discovered in mammals (Larsen et al, 2017a(Larsen et al, , 2017b. This family is comprised of four tetratricopeptide repeat (TPR)-containing proteins that appear to be ER polytopic transmembrane proteins called TMTC1-4 (transmembrane and TPR-containing proteins 1-4) (Della-Morte et al, 2011;Racapé et al, 2011;Cao et al, 2012;Sunryd et al, 2014;Larsen et al, 2017a;Li et al, 2018). TMTC1, 2 and 4 are ER proteins involved in Ca 2+ regulation as they associate with ER Ca 2+ re-uptake pump SERCA2B (Sunryd et al, 2014;Li et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation